Effectiveness Of Neuromuscular Training Program In Young Athletes Suffering From Lower Lateral Ankle Ligament Injury. - Deivendran, Kalirathinam; Soumendra, Saha; Taran, Singh (2016)
The perception and execution of musculoskeletal control and movement are mediated primarily by the central nervous system and involve the integration of 3 main subsystems: somatosensory, vestibular, and visual. Balance performance and its measurement are influenced by these sub-systems. This present study was carried out to investigate the effectiveness of, neuromuscular controlled training exercises comprising bosu-ball balance training and conventional physiotherapy exercise training protocols on the level of stability, balance and proprioception in the athletes, diagnosed with lateral ligament injury of ankle joint. The Y Balance test was used as a reliable and valid tool for quantitative balance assessment. Thirteen players (aged between 19 to 26 years, Mean age = 23.2; SD = 2.46) suffering from grade II & grade III lateral ligament injury were recruited from the OPD of the department of Orthopaedics, of the Hospital of Universiti Sains Malaysia. All of the participants were subjected to pre-intervention or baseline assessments, comprising of Y-balance test and assessment of proprioception employing Biodex 4 Isokinetic Equipment. Thereafter participants were introduced with neuromuscular controlled training program, which was imparted for 12 sessions (30 min/day; 2 days/wk. for 6 wk.). Findings of the study revealed that 6 weeks of neuromuscular exercises training significantly improved the balance and some significant aspects of proprioception observed amongst the young athletes diagnosed with ankle lateral ligament injury.